UPAYA PENINGKATAN MOTIVASI BELAJAR PKN DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE INDEX CARD MATCH SISWA KELAS VI SDN 015 PAGARAN TAPAH DARUSSALAM - Asma Nababan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research is motivated by the lack of student motivation class VI SDN 015 Pagaran TapahDarussalam. Goals to be achieved in this research is to increase the motivation to learn civicsstudent class VI SDN 015 Pagaran Tapah Darussalam through Learning cooperativelearning type of index card match held for 1 month. This research was conducted in SDN 015Pagaran Tapah Darussalam. Classes that thorough research is a class VI student number asmany as 27 people. This classroom action research was started in March 2015. This form ofresearch is classroom action research. The research instrument consists of instrumentsteacher and student activity sheets and achievement test. Based on the analysis and discussionas presented in chapter IV can be concluded that with the implementation of cooperativelearning method type type index card match can increase student motivation to learn civicsclass VI SDN 015 Pagaran Tapah Darussalam. This success is due to the use of cooperativelearning method type of index card match students become more increased activity and thestudents take pleasure in learning. It is the show of the results of the first cycle study oflearning motivation reached an average of 68.5% and emningkat the second cycle to anaverage of 84.6% with a high category. Under these conditions, the enrollment rate willincrease and in turn can increase learning motivation